2004
DOI: 10.1381/0960892041590854
|View full text |Cite
|
Sign up to set email alerts
|

Manometric Abnormalities and Gastroesophageal Reflux Disease in the Morbidly Obese

Abstract: Prevalence of manometric abnormalities in the morbidly obese is high. Presence of a nut cracker-like distal esophagus in the morbidly obese is significant and warrants further evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
48
2
7

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(64 citation statements)
references
References 15 publications
7
48
2
7
Order By: Relevance
“…High intra-abdominal pressure due to abdominal fat accumulation has been reported to result in an increased gastroesophageal pressure gradient and subsequently facilitate the development of hiatal hernia (10)(11)(12)(13)(14). Among the present male subjects, BMI and the prevalence of diaphragmatic hiatus increased in a concomitant manner during the study period.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…High intra-abdominal pressure due to abdominal fat accumulation has been reported to result in an increased gastroesophageal pressure gradient and subsequently facilitate the development of hiatal hernia (10)(11)(12)(13)(14). Among the present male subjects, BMI and the prevalence of diaphragmatic hiatus increased in a concomitant manner during the study period.…”
Section: Discussionmentioning
confidence: 63%
“…GERD has been becoming more prevalent in Asian populations in recent decades, and although the disease is considered to be a common disorder in both Western and Asian populations, its increasing prevalence in Asia may be due to multiple factors, such as the Westernization of eating habits, decrease in the rate of Helicobacter pylori infection, increased gastric acid secretion and a larger elderly population, as well as other factors (2)(3)(4)(5)(6)(7)(8)(9). High intra-abdominal pressure caused by abdominal fat accumulation has been demonstrated to increase the gastroesophageal pressure gradient and incidence of gastroesophageal reflux, while obesity and a high body mass index (BMI) have repeatedly been reported to be correlated with a high prevalence of reflux esophagitis and symptoms of GERD (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). On the other hand, gender differences related to chronological changes in BMI and the prevalence of GERD have not been investigated in Japanese subjects, although a male predominance has been shown to be related to the frequency of reflux esophagitis and GERD (2-5, 8, 9).…”
Section: Introductionmentioning
confidence: 99%
“…Hiatal hernia was diagnosed by the presence of a gastric wall above the diaphragmatic hiatus, which was unaccompanied by underlying longitudinally arrayed vessels, as already described in our previous publication (18) T a b l e 1 . Ch a r a c t e r i s t i c s o f S u b j e c t s (1,13,15,18,(20)(21)(22)(23)(24)(25)(29)(30)(31)(32) …”
Section: Gastroesophageal Reflux Disease (Gerd) Is Characterized By Tmentioning
confidence: 99%
“…An increased gastroesophageal pressure gradient and hiatal hernia development have been reported to be induced by a high intra-abdominal pressure due to abdominal fat accumulation (3)(4)(5)(6)(7), while obesity and a high body mass index (BMI) have repeatedly been demonstrated to be associated with the high prevalence of reflux esophagitis and GERD symptoms (8)(9)(10)(11)(12)(13)(14)(15). In addition, metabolic syndrome, diagnosed by the presence of visceral fat accumulation, dyslipidemia, hypertension, and hyperglycemia, has been demonstrated to correlate with the occurrence of GERD (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Signs and symptoms include swollen gums, deepening of gingival crevices leading to the formation of periodontal pockets, bleeding on brushing, increased spacing between teeth, and loose teeth. Recent studies have indicated that periodontitis is closely correlated with systemic disorders, such as obesity, metabolic syndrome and cardiovascular diseases (19,20), which have also been demonstrated to have a positive relationship with GERD occurrence (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). In addi-tion, periodontitis may induce or worsen GERD, since saliva secretion, which is influenced by oral hygiene including the periodontal status, has been demonstrated to be associated with GERD (21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%